Physical modification of biochar to expose the inner pores and their functional groups to enhance lead adsorption - Fahmi, Alaa Hasan; Abd Wahid, Samsuri; Jol, Hamdan; Karam Singh, Daljit Singh (The Royal Society of Chemistry, 2018)
Biochars have been successfully used to treat wastewater and contaminated soils. The efficiency of biochar as a biosorbent of heavy metals can be increased by reducing the particle size, exposing the inner pores and their functional groups. In this study, the empty fruit bunch biochar (EFBB) of oil palm was separated into three particle sizes, fine (F-EFBB < 50 μm), medium (M-EFBB 250–500 μm) and coarse (C-EFBB > 2000 μm) to compare their physical and chemical characteristics and their adsorption capacity for lead. Results revealed that the F-EFBB had greater surface area and exposed more micropores compared to the other particle sizes. Similarly, the F-EFBB had the most oxygen containing functional groups, CEC, and negative charges as measured by the zeta potential. The F-EFBB had the highest adsorption capacity for Pb, followed by M-EFBB and C-EFBB with the lowest. Therefore, the F-EFBB are able to adsorb more heavy metals as compared to M-EFBB and C-EFBB, as suggested by the more favourable physical and chemical characteristics.